Planar Alignment of Graphene Sheets by a Rotating Magnetic Field for Full Exploitation of Graphene as a 2D Material. (25th September 2018) - Lin, Feng; Yang, Guang; Niu, Chao; Wang, Yanan; Zhu, Zhuan; Luo, Haokun; Dai, Chong; Mayerich, David; Hu, Yandi; Hu, Jonathan; Zhou, Xufeng; Liu, Zhaoping; et al.
Abstract: Planar alignment of disc‐like nanomaterials is required to transfer their superior anisotropic properties from microscopic individual structures to macroscopic collective assemblies. However, such alignment by electrical or magnetic field is challenging due to their additional degrees of orientational freedom compared to that of rod‐like nanostructures. Here, the realization of planar alignment of suspended graphene sheets using a rotating magnetic field produced by a pair of small NdFeB magnets and subsequent demonstration of high optical anisotropy and potential novel device applications is reported. Compared to partially aligned sheets with a static magnetic field, planar aligned graphene suspensions exhibit a near‐perfect order parameter, much higher birefringence and anisotropic absorption/transmission. A unique feature of discotic nanomaterial assemblies is that the observed order parameter and optical property can vary from isotropic to partial and complete alignment depending on the experimental configuration. By immobilizing and patterning aligned graphene in a UV‐curable polymer resin, we further demonstrated an all‐graphene permanent display, which exhibits wide‐angle, high dark‐bright contrast in either transmission or reflection mode without any polarizing optics. The ability to control and pattern graphene orientation in all three dimensions opens up new exploration and broad device applications of graphene. Abstract : Planar alignment of suspended graphene sheets is realized with a near‐perfect order parameter and high optical anisotropy by using a rotating magnetic field produced by a pair of small NdFeB magnets, and can be further patterned and immobilized by photolithography. The arbitrary orientational and spatial control has enabled a wide range of device applications of graphene and related materials.